Strategi Kepala Sekolah Dalam Pengembangan Mutu Lembaga Pendidikan Islam Sma Al Izzah International Islamic Boarding Shcool (Iibs) Kota Batu - Nurul Yaqien (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The principal's strategy in developing the quality of education is one of the efforts in realizing superior educational institutions. The excellence of educational institutions is one of the main keys in educating the nation's children to enter the global world. Without the provision of quality education, it will be difficult to obtain a generation that is superior and competitive in their field. The purpose of this study was to analyze and find strategies used by school principals in developing the quality of Islamic education at SMA Al Izzah International Islamic Boarding School Batu City. The research method used is a qualitative approach with the type of case study research. While the research paradigm uses interpretive.1). The existence of a communication strategy that aims to carry out a smooth and professional communication pattern; 2) There is a strategy of cooperation, between vice principals (internal) and cooperation with external parties (external). 3). There is a tutoring strategy, to train students to get used to working on predictive questions for the Olympics, national exams and college entrance exams; 4). There is a target deposit strategy, to fulfill the students' memorization of the Qur'an according to their respective grade levels; 5). There is a strategy to enter state universities through the invitation route; 6).The existence of a quality culture strategy to be formedawareness of every school community to improve the quality of the institution; 7). There is an evaluative strategy that aims to find out some breakthroughs so that students can enter state universities (PTN) that are favorite and in demand both nationally and internationally.